ANALYSIS OF FACTORS AFFECTING MORALE SPRIRIT OF WORK - Rahmad Bahagia; Linzzy Pratami Putri (CERED Indonesia Institute, 2021)
This study aims to see what factors affect employee morale in Medan City during the COVID-19 pandemic. The population in this study were all private employees in the city of Medan with the sampling technique using accidental samples, where the sample in this study was conducted by 100 people. The research method used is descriptive quantitative using factor analysis techniques. Where from the results of the research conducted there were only 4 (four) dominant factors that influenced morale during the Covid 19 pandemic, namely Compensation, Ability, Motivation, and Leadership.